PENGARUH MANAJERIAL KEPALA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP KOMPETENSI GURU DI SEKOLAH DASAR NEGERI KECAMATAN SALATIGA KABUPATEN SAMBAS - Eswandi yarso; H.M. Chiar; Wahyudi Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study in general aimeds to reveal the managerial influence of principals and the academic supervision on the competent of teachers at the SD Negeri Salatiga District. This study used a quantitative approach. The data used were quantitative data. The population as well as the sample in this study amounted to 95 teachers. Data was collected using a questionnaire with a measurement model using a Likert scale. The collected data is tabulated. Then the analysis was done using the help of a computer application program, namely SPSS version 16 for Window. Data analysis used descriptive statistics and inferential statistics.The first step in testing the hypothesis, namely the test requirements for regression analysis (normality test and linearity test). After testing the analysis requirements were met, then testing the hypothesis. The analysis technique used was multiple regression analysis. To determine the effect of independent variables on non-independent variables together, the F test is used.The results showed that 1) the principal managerial influence (X1) with teacher performance competent (Y) Beta (b1) amounted to 0.343 = 33.40%, 2) the effect of the principal's cademic supervision (X2) on teacher competent (Y) Beta (b1 ) equal to 0.442 = 44.20%, 3) managerial influence of the principal (X1) and the academic supervision (X2) on teacher competent by 0.554 or 55.40%. The results of the F test seen in the ANOVA output from the results of multiple linear regression analysis indicated that Fcount> Ftable (45,959> 3,115) Keywords :  Academic Supervision Principal Managerial,  Teacher Competent